Intervención del terapista respiratorio en paciente masculino de 54 años de edad con insuficiencia respiratoria aguda. - Moyano Molina, Génesis Geraldine (2022)
This clinical case study is based on a 54-year-old male patient who is taken to the IESS Babahoyo hospital by an ambulance from the fire department in the company of his family member with oxygen support through a simple mask presenting tachycardia and respiratory distress. He is admitted by emergency where he remains in the hydration area, a peripheral line is channeled and established to pass his medication, in addition, vital signs are controlled and laboratory samples are taken. The relative reports that the patient has a surgical history since 2 years ago he underwent cervical lymph node cancer, after which radiotherapy and chemotherapy were performed. In 2020 he was diagnosed with pulmonary metastasis, continuing treatment with chemotherapy. Subsequently, the patient is taken to the observation area where an oncology assessment was carried out, who indicated performing a tomography, showing images of balloon release in both lung fields; disease in frank progression without favorable response to chemotherapy treatment. The next day of his stay in the observation area, his respiratory difficulty increased, presenting desaturation, intense pain and tachycardia. Pain therapy was instituted and the oxygen device was changed to a reservoir mask. On the third day, the patient presented severe respiratory distress requiring endotracheal intubation and mechanical ventilatory support. Family members were informed who refused the medical request, signing the documents ordering no intubation and no resuscitation. As the hours passed, patients went into cardiorespiratory arrest.